2000
DOI: 10.1063/1.1289904
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mapping and formation of V-defects in InGaN multiple quantum wells

Abstract: InGaN multiple-quantum-well structures grown by metal–organic chemical-vapor deposition on GaN and capped by p-type GaN are found to contain inverted pyramids of indium-free GaN. High-resolution structural and chemical analyses of these “V-defects” by a number of complementary transmission electron microscopy techniques show that the InGaN quantum wells end abruptly at the V-defect interfaces, which lie on {10–11} planes. Each V-defect has at its center a threading edge dislocation, indicating that the defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 11 publications
7
93
1
Order By: Relevance
“…The slightly higher pit density found for the sample with an InGaN UL leaves us with two partial conclusions: (i) we cannot conclude that the InGaN UL reduces the dislocation density and (ii) the InGaN UL promotes the pit formation because of the lower surface energy of the InGaN alloy. 17 At first sight, our results seem to be consistent with the dislocationscreening mechanism induced by the formation of V-defects at the dislocation surface termination, 13 as proposed in a couple of papers. 12,18 To clarify this point, we moved to FS GaN substrates for which the dislocation density ($10 6 cm…”
supporting
confidence: 75%
“…The slightly higher pit density found for the sample with an InGaN UL leaves us with two partial conclusions: (i) we cannot conclude that the InGaN UL reduces the dislocation density and (ii) the InGaN UL promotes the pit formation because of the lower surface energy of the InGaN alloy. 17 At first sight, our results seem to be consistent with the dislocationscreening mechanism induced by the formation of V-defects at the dislocation surface termination, 13 as proposed in a couple of papers. 12,18 To clarify this point, we moved to FS GaN substrates for which the dislocation density ($10 6 cm…”
supporting
confidence: 75%
“…3 The subtraction of the characteristic background contribution from the postedge region in EELS result yields an elemental map that may be regarded as quantitative in nature. 3,4 The ratio of In and Ga elemental maps obtained by the earlier method, multiplied by a correction factor to account for the differing inelastic scattering cross sections involved, produces an atomic-ratio map ͑In/Ga ratio͒ which is selfnormalizing for both thickness and elastic effects. In addition, plural scattering deconvolution techniques may be applied to improve the quantitative accuracy of calculated elemental maps and the TEM thickness problem was corrected using the corresponding t/ map calculated from the low-loss data.…”
mentioning
confidence: 99%
“…Significant improvement of the AlN crystal quality using Lateral Epitaxial Overgrowth (LEO) of AlN on sapphire substrates was also demonstrated . This resulted in 214 nm stimulated emission, the shortest wavelength stimulated emission reported in semiconductor materials (Shatalov et al, 2006). AlN is widely used as the buffer layer for Ultraviolet (UV) Light Emitting Diodes (LED) and High Electron Mobility Transistors (HEMT) grown on SiC substrates currently due to its small lattice constant, wide bandgap and high thermal conductivity (Chen et al 2009a;Chen et al 2009b).…”
Section: Aln Growth Condition Optimizationmentioning
confidence: 99%
“…4. www.intechopen.com It is usually accepted that the high defect density in GaN leads to poor optical property and also affects the structural and optical quality of the active layer composed of the InGaN/GaN MQWs. It has been reported that threading dislocations disrupt the InGaN/GaN MQW and initiate the V defect using transmission electron microscopy (TEM) and atomic force microscopy (AFM) (Sharma et al, 2000 ;Lin et al, 2000). Several research groups have reported that there is always a threading dislocation (TD) connected with the bottom of V defect and the cause of V-defect formation is the increased strain energy and the reduced Ga incorporation on the [ ] pyramid planes compared with the [0001] plane (Sun et al, 1997).…”
Section: V-shape Defect In Inganmentioning
confidence: 99%